2020
DOI: 10.26740/bisma.v13n1.p26-37
|View full text |Cite
|
Sign up to set email alerts
|

Service quality and store atmosphere on customer satisfaction and repurchase intention

Abstract: Nowadays, consumers are not only looking for good tastes, but they are also looking for a cosy cafe atmosphere and satisfying service. The high competition in the culinary business has forced entrepreneurs to offer different concepts to attract customers. This study will give an account of analyzing the role of cafe atmosphere, service quality and customer satisfaction in customer purchase intention in thematic cafe in Surabaya. This study involved 150 respondents with PLS-SEM was used to analyze the data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…The results of (R. Arlanda, 2018) research show that customer satisfaction positively affects repurchase intention. Customer satisfaction also significantly influences customer intention to repurchase (Soebandhi et al, 2020). Based on this explanation, the hypothesis can states as follows:…”
Section: Customer Satisfaction and Repurchase Intentionmentioning
confidence: 92%
“…The results of (R. Arlanda, 2018) research show that customer satisfaction positively affects repurchase intention. Customer satisfaction also significantly influences customer intention to repurchase (Soebandhi et al, 2020). Based on this explanation, the hypothesis can states as follows:…”
Section: Customer Satisfaction and Repurchase Intentionmentioning
confidence: 92%
“…Thus, it can be concluded that the higher the level of service quality will affect the higher level of visits. This shows that commitment to reuse services and willingness to pay more for services is influenced by the services provided (Soebandhi et al, 2020). From the description above, the following hypothesis can be formulated: H2: Service quality affects revisit intention positively and significantly.…”
Section: Service Quality and Revisit Intentionmentioning
confidence: 95%
“…Good service is also an indication to increase customer satisfaction. This shows that commitment to reuse services and willingness to pay more for services is influenced by the services provided (Soebandhi et al, 2020). Service quality is the totality of the characteristics and characteristics of a product or service that support its ability to meet needs directly or indirectly.…”
Section: Service Qualitymentioning
confidence: 99%
See 2 more Smart Citations